The Effects of Personal Values and Sustainable Fast Fashion Consumption Beliefs on Clothing Reuse Behaviour: The Moderating Roles of Facilitating Conditions and Habits - Loi, Wai Yee (2017)
The rapid development of fast fashion trend has greatly contributed to the global economy, nevertheless, it has immensely brought the ecological impacts in the global environment, such as throw-away culture and wasteful clothing disposal. Despite the growing interest and awareness of environmental sustainability issues, majority of the consumers are yet to practise pro-environmental clothing consumption and disposal actions. Due to the values-actions gap, the present study aimed to investigate the relationship of personal values, sustainable fashion consumption beliefs (SFCB), facilitating conditions, habits and the consumers’ clothing reuse behaviour (CRB) by underpinning Value-Belief-Norm Theory (VBN) and Theory of Interpersonal Behaviour.